Collapse probability of code-based design of a seismically isolated reinforced concrete building. (October 2021) - Güneş, Necmettin; Ulucan, Zülfü Çınar
Abstract: In this study, the collapse probability of a Reinforced Concrete (RC) seismically isolated building designed according to ASCE 7-16 is given using the Incremental Dynamic Analysis (IDA) and Adaptive Incremental Dynamic Analysis (AIDA) methods. In a region where spectral demands of different intensity levels are known, thirty ground motions are selected and gradually changed from first to last seismic intensity level to match hazard-consistent properties in the extreme events, as given in the AIDA procedure. The collapse probabilities were obtained using FEMA P695 based IDA and AIDA methods by unidirectional analysis results, separately. The fragility curve obtained using bidirectional analysis results of the AIDA method was adjusted to the fragility curve acquired utilizing unidirectional analysis results by a correction factor to consider the accidental torsion effects. It is determined that the collapse probability of isolators is over the ASCE 7-16 acceptable limit, which is 10% for building in Risk Category of I and II at the Risk-Targeted Maximum Considered Earthquake (MCER ) level. Also, it is shown that reducing the displacement capacity of isolators according to ASCE 7-16 causes the probability of collapse to exceed the 10% limit considerably. When the displacement capacity was increased to 1.25 times of total maximum displacement, the collapse probability decreases below the acceptable limit at the MCER level. The analysis results reveal that the collapse probability of isolators is sensitive to ground motion suites. Despite the isolator displacement capacity, the fragility curves of the superstructure drift demands, beam plastic rotations, and column tensile strains provide sufficient exceedance probabilities at the MCER level.